Patterns and outcomes of patients with abdominal injury: a multicenter study from Iran - Sara Mirzamohamadi; Mohammad Navid HajiAbbasi; Vali Baigi; Payman Salamati; Vafa Rahimi-Movaghar; Mohammadreza Zafarghandi; Mehdi Nasr Isfahani; Esmaeil Fakharian; Seyed Houssein Saeed-Banadaky; Morteza Hemmat; Akram Zolfaghari Sadrabad; Salman Daliri; et al. (BMC Emergency Medicine, 2024)
Abstract Background Injury is one of the leading causes of death worldwide, and the abdomen is the most common area of trauma after the head and extremities. Abdominal injury is often divided into two categories: blunt and penetrating injuries. This study aims to determine the epidemiological and clinical characteristics of these two types of abdominal injuries in patients registered with the National Trauma Registry of Iran (NTRI). Methods This multicenter cross-sectional study was conducted with data from the NTRI from July 24, 2016, to May 21, 2023. All abdominal trauma patients defined by the International Classification of Diseases; 10th Revision (ICD-10) codes were enrolled in this study. The inclusion criteria were one of the following: hospital length of stay (LOS) of more than 24 h, fatal injuries, and trauma patients transferred from the ICU of other hospitals. Results Among 532 patients with abdominal injuries, 420 (78.9%) had a blunt injury, and 435 (81.7%) of the victims were men. The most injured organs in blunt trauma were the spleen, with 200 (47.6%) and the liver, with 171 (40.7%) cases, respectively. Also, the colon and small intestine, with 42 (37.5%) cases, had the highest number of injuries in penetrating injuries. Blood was transfused in 103 (23.5%) of blunt injured victims and 17 (15.2%) of penetrating traumas (p = 0.03). ICU admission was significantly varied between the two groups, with 266 (63.6%) patients in the blunt group and 47 (42%) in penetrating (p < 0.001). Negative laparotomies were 21 (28%) in penetrating trauma and only 11 (7.7%) in blunt group (p < 0.001). In the multiple logistic regression model after adjusting, ISS ≥ 16 increased the chance of ICU admission 3.13 times relative to the ISS 1–8 [OR: 3.13, 95% CI (1.56 to 6.28), P = 0.001]. Another predictor was NOM, which increased ICU chance 1.75 times more than OM [OR: 1.75, 95% CI (1.17 to 2.61), p = 0.006]. Additionally, GCS 3–8 had 5.43 times more ICU admission odds than the GCS 13–15 [OR:5.43, 95%CI (1.81 to 16.25), P = 0.002] respectively. Conclusion This study found that the liver and spleen are mostly damaged in blunt injuries. Also, in most cases of penetrating injuries, the colon and small intestine had the highest frequency of injuries compared to other organs. Blunt abdominal injuries caused more blood transfusions and ICU admissions. Higher ISS, lower GCS, and NOM were predictors of ICU admission in abdominal injury victims.